Canine dystocia in 50 UK first‐opinion emergency care veterinary practices: clinical management and outcomes. (30th March 2019) - O'Neill, Dan G; O'Sullivan, Aoife M; Manson, Erin A; Church, David B; McGreevy, Paul D; Boag, Amanda K; Brodbelt, Dave C
Abstract : Canine dystocia is a relatively common veterinary presentation. First opinion emergency care clinical data from 50 Vets Now clinics across the UK were used to explore dystocia management and outcomes in bitches. Caesarean section (CS) was performed on 341/701 (48.6 per cent (95 per cent CI 44.9 to 52.4)) of dystocia cases. The bulldog (OR 7.60, 95 per cent CI 1.51 to 38.26, P=0.014), Border terrier (OR 4.89, 95 per cent CI 0.92 to 25.97, P=0.063) and golden retriever (OR 4.07, 95 per cent CI 0.97 to 17.07, P=0.055) had the highest odds of CS among dystocic bitches compared with crossbreds. Brachycephalic dystocic bitches had 1.54 (95 per cent CI 1.05 to 2.28, P=0.028) times the odds of CS compared with non‐brachycephalics. Oxytocin was administered to 380/701 (54.2 per cent) and calcium gluconate was administered to 82/701 (11.7 per cent) of dystocic bitches. 12 of 701 dystocia cases (1.7 per cent) died during emergency care. These results can help veterinary surgeons to provide better evidence on the risks to owners who may be contemplating breeding from their bitches. In addition, the results on the management and clinical trajectory of dystocia can facilitate clinical benchmarking and encourage clinical audit within primary care veterinary practice.